Identification of antibodies to Leptospira spp. in the spot-legged turtle (Rhinoclemmys punctularia) maintained in captivity - Katarine de Souza Rocha; Ianny Watuzy Monteiro Baia; Louysse Helene Monteiro; Juliana Maria Santos Miranda; Thamillys Rayssa Marques Monteiro; Andréia Ferreira da Silva; Thalita Amaral dos Reis; Maeli Fernanda Silva Ferreira; Ellen Yasmin Eguchi Mesquita; Carla Cristina Guimarães de Moraes (Semina: Ciências Agrárias, 2019)
Leptospirosis is a zoonosis of worldwide distribution in which the agent can infect several animal species and accidentally humans. In view of the limited number of studies on anti-Leptospira antibodies in wild animal species, especially those living in aquatic environments, we sought in this study to investigate the presence of these antibodies in the spot-legged turtle (Rhinoclemmys punctularia) maintained in captivity in the Rodrigues Alves Botanical Garden–Amazon Zoobotanical Park, located in Belém, Pará State, Brazil. Serum samples were collected from 31 turtles, and identification of anti-Leptospira antibodies was performed using the microscopic agglutination test, using a collection of 31 live antigens which represent 19 serogroups of Leptospira. Among the analyzed samples, 54.83% (17/31) were observed to be reactive, and co-agglutination was detected in a further six samples which were not accounted for in the frequency of serogroups. The most frequently detected serogroups were Tarassovi 72.72% (8/11), Celledoni 18.18% (2/11), and Pomona 9.09% (1/11)], with titers ranging from 200 to 400, being this the first study to report infection of these serogroups in this species of chelonios. The animals were kept in water tanks, which probably favored the transport of the agent and allowed its transmission to the spot-legged turtle. We thus confirmed presence of anti-Leptospira antibodies in chelonians maintained in the Rodrigues Alves Botanical Garden.